Integrating TikTok as a 21st Century Learning Innovation: A Quasi-Experimental Study on Student Engagement and Learning Outcomes - Eka Lukitasari; Dhany Efita Sari (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study aims to examine the effectiveness of using TikTok as a 21st-century learning innovation on students' learning outcomes and engagement in the Spreadsheet subject. The research employed a quantitative approach with a quasi-experimental nonequivalent control group design. The research population consisted of all tenth-grade students of Accounting and Institutional Finance (AKL) at SMK Negeri Banyudono, Boyolali, while the sample comprised 72 students selected through cluster random sampling. Class X AKL 1 was designated as the experimental group receiving TikTok-based instruction, whereas Class X AKL 2 served as the control group with conventional learning methods. Research instruments included learning outcome tests (pre-test–post-test) and a learning activeness questionnaire that met validity and reliability criteria. Data were analyzed using paired sample t-tests and independent sample t-tests. The results indicated a significant difference between the two groups after treatment, with the experimental group showing greater improvements in learning outcomes and student engagement. These findings demonstrate that TikTok is an effective learning medium, enhancing student participation and understanding and contributing to the development of vocational education literature by providing empirical evidence of digital technology integration in the learning process.